Natural Products as Leads for Neglected Trophical Diseases (NTDs) Treatment; A Chemical and Biological - Review - Mathew, Twan Sale; Chinedu, Emmanuel Kinsley; Haladu, Muhammed; Abubakar, Musa Yahaya; Adam, Ansar Bilayamin; Shamsuddeen, Ruslan (Darul Yasin Al Sys, 2024)
Natural compounds are mostly found in medicinal plants that are used to treat various ailments. They are distinguished by their structural complexity and diversity, which span a wide chemical universe and present both benefits and shortcomings to the process of discovering novel drugs. Neglected tropical diseases (NTDs) are common tropical diseases that impact over one billion people globally. Numerous pathogens, such as bacteria, fungi, viruses, parasites, and poisons, are responsible for them. Natural products have always been important in the search for new drugs to treat differents diseases including NTDs. The purpose of this chapter is to provide an update on the evaluation of both the chemical and biological properties of natural compounds that have been extracted and identified from plant sources, and may be utilized as viable candidates for the development of new drugs treat NTDs with lower incidence such as: Buruli ulcer, dracunculiasis, echinococcosis, food-borne trematodiases, leprosy, lymphatic filariasis, parasitics, schistosomiasis, soil-transmitted helminthiases, taeniasis/cysticercosis, trachoma and yaws. This chapter also intends to make a critical review on the chemical analysis of natural products’ structure and classification, biological evaluation of natural products’ antiparasitic, anti-inflammatory and immunomodulatory activities. In conclusion, Natural products continue to be a key source of fresh ideas for treating NTDs. Their distinct methods of action and variety of chemicals offer potential for the development of new treatments.